تحليل أداء بعض بروتوكولات التحكم بأخطاء الإرسال عند استخدامها في القناة الفضائية للربط بين محطات VSATs عبر محطة HUB مركزية - علي صادق; أحمد علي; حلّوم سهاد (Latakia University Journal -Engineering Sciences Series, 2019)
يتضمن البحث تحليل أداء القناة الفضائية عند استخدام البروتوكولات المعتمدة في الاتصالات الأرضية للتحكم بأخطاء الإرسال، وذلك بسبب خصوصية الاتصالات الفضائية، والتي تظهر بشكل أساسي في كل من: 1- أزمنة التأخير الكبيرة في الوصلات الفضائية مقارنة بالاتصالات الأرضية، والتي تعود إلى بعد المسافة مابين المرسل والمستقبل. 2- معدل خطأ الخانة BER (bite error rate) المرتفع في الوصلات الفضائية بالنسبة للاتصالات الأرضية، وذلك نظراً لطبيعة القناة الفضائية. اعتمد البحث على دراسة قناة فضائية تربط بين محطات أرضية من نوع VSAT (very small aperture terminal) عبر محطة مركزية ,HUBباعتبار أن محطة الـ VSAT أو محطة الـ HUB تمثل عقداً (nodes) في الشبكة المرجوة، فقد ركزنا في الدراسة على الطبقات الثلاث الدنيا في نموذج الطبقات السبع OSI وخصوصاً طبقة وصلة المعطيات (Data link) لأنها تحتوي على البروتوكولات المسؤولة عن إيصال البيانات بشكل موثوق وصحيح إلى المستقبل عن طريق التحكم بالكشف عن الأخطاء، إضافة إلى تحكمها بآلية الإرسال. لقد تم تحليل عمل البروتوكولات ضمن هذه الطبقات من أجل الوصول إلى البروتوكول المناسب للقناة الفضائية وفق نوع المعلومات المنقولة وحجمها ومعدلات إرسالها، وذلك من أجل تحقيق الاستخدام الفعال للقناة الفضائية، وبالتالي تخفيض التكلفة الاقتصادية الناتجة من الاستثمار غير الفعال للقناة الفضائية. This research contains an analysis of the performance of satellite channel while using the error control protocols which are used in terrestrial communication because of the specialty of satellite communication which appears basically in: The great delay in the satellite links comparing with the terrestrial communication which is caused by the large distance between the transmitter and receiver. The bit error rate (BER) in the satellite links is higher than it is in terrestrial one which is caused by the nature of satellite channel. The research is based on a study of the satellite channel which connect between VSATs through central station (HUB). Taking in consideration that the VSAT and HUB represent nodes in the network, we studied the three lower layers in OSI model especially data link layer which is contains the protocols which deliver the data in a successful and reliable way to the receiver by detecting the errors in addition to controlling the access to the channel. We have analyzed those layers’ protocols to achieve suitable protocol for the satellite channel according to the transported data types, their sizes and their bit rate in order to achieve the most useful use of the satellite channel which in turn leads to reducing the cost which is usually caused by the improper investigation of the satellite channel.